2012
DOI: 10.1007/s00438-012-0674-z
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes within a 143 kb region of the flower sex locus in Vitis

Abstract: Wild Vitis species are dioecious plants, while the cultivated counterpart, Vitis vinifera subspec. vinifera, generally shows hermaphroditic flowers. In Vitis the genetic determinants of flower sex have previously been mapped to a region on chromosome 2. In a combined strategy of map-based cloning and the use of the publicly available grapevine reference genome sequence, the structure of the grapevine flower sex locus has been elucidated with the subsequent identification of candidate genes which might be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
140
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(160 citation statements)
references
References 44 publications
(56 reference statements)
11
140
0
Order By: Relevance
“…Plant species with homomorphic sex chromosomes so far investigated have been found to have a SDR < 1% of the total length of the Y chromosome, e.g., Vitis vinifera [44,45], several Populus species [46,47], and Fragaria chiloensis [48]. Mercurialis annua thus appears to have a particularly large SDR for a species with homomorphic sex chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Plant species with homomorphic sex chromosomes so far investigated have been found to have a SDR < 1% of the total length of the Y chromosome, e.g., Vitis vinifera [44,45], several Populus species [46,47], and Fragaria chiloensis [48]. Mercurialis annua thus appears to have a particularly large SDR for a species with homomorphic sex chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several genetic maps based on interspecific crosses have confirmed that sex determinism in the genus Vitis is under the control of a single major genomic region located on chromosome 2, close to the SSR marker VVIB23 [1517]. Recently, a complex interspecific cross ( V. vinifera x [ V. riparia x V. cinerea ]) was used by Fechter et al [18] to narrow the location of the sex locus to a 143 kb genomic region located between positions 4.907.434 and 5.037.597 bp of chromosome 2 [18] on the physical map of the V. vinifera reference genome sequence (PN40024 12x.0 version [19]). So far, the co-localisation on chromosome 2 of the sex locus in V. vinifera subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the processes involved in sex chromosome evolution, as the suppression of genetic recombination or the genetic degeneration of the Y chromosome, are not well understood and only the study of the sex-determining systems on different species and at different steps of evolution could provide some answers [23]. While the sex determination locus in Vitis species was mainly studied to develop genetic markers for early sexing for breeding purposes [18,20], the work of Fechter et al [18], evidencing a small sex-determination region, suggests that Vitis species could be good candidates to study the early steps of sex chromosome evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Two additional markers were used for flower sex determination: VVIb23 (Fechter et al. 2012) and APT3 (Battilana et al. 2013).…”
Section: Methodsmentioning
confidence: 99%